Optimizing Partnership Operational Processes at SEAMOLEC South Tangerang Through Customer Relationship Management - Muhammad Farhan Abdillah; Septian Sony Utomo (Community Development and Empowerment, 2026)
This community service journal documents the operational optimization of partnership management at SEAMEO Regional Open Learning Centre (SEAMOLEC) South Tangerang through the implementation of the Independent Merdeka Belajar Kampus Merdeka (MBKM) Internship program. The Community Partnership Division faced administrative challenges due to decentralized collaboration data, the risk of delays in updating Memorandums of Understanding (MoUs), and inconsistencies in monitoring schedules. To address these issues, a cloud-based database system using Google Sheets was designed to integrate all partnership variables in real-time. The implementation method of this community service consisted of five main phases: field survey, problem identification, database design, data implementation, and system evaluation. The program results showed a significant increase in efficiency, where the search time for cooperation documents was cut by up to 90%, and tracking the status of cooperation achieved 100% accuracy. The application of Customer Relationship Management (CRM) principles and continuous quality management successfully strengthened external communication and maintained the loyalty of strategic partners. This program proves that the integration of information technology in partnership administration governance can create a regional collaboration ecosystem that is more productive, responsive, and accountable.